Personal Data Protection Vulnerabilities In Cybercrime Sniffing Bank Account Break-Ins - Setiawati, Diana; Permata Dewi, Tyas; Ayu Astutik, Zulfiana (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2024)
Cybercrime, particularly Sniffing, poses a hazard in the digital age since attackers illegally breach customers' data, resulting in losses and widespread concern. This study aimed to clarify the legal protections available to victims of sniffing cybercrimes and the banks' obligations to their clientele. This study includes primary, secondary, and tertiary legal materials with a normative legal approach. The analytical method produced information through descriptive analysis using qualitative methodologies. The research findings demonstrated that, despite the lack of a required special institution and ambiguity surrounding accountability in resolving disputes deemed harmful to customers, Law No. 27 of 2022 and Bank Indonesia Regulation No. 3 of 2023 indicated that there was legal protection for customers' data. As a result, customers must take greater precautions to protect their data.